Neurobiological predictors for clinical trajectories in fully remitted depressed patients. Issue 4 (1st November 2020) - Blank, Thomas S.; Meyer, Bernhard M.; Rabl, Ulrich; Schögl, Paul; Wieser, Marie‐Kathrin; Pezawas, Lukas
Abstract: Background: Serious long term health and economic detriment accompany residual depressive symptoms even in fully remitted depressed patients (rMDD). Neurobiological predictors for rMDD patients' illness trajectory are absent. Methods: rMDD patients ( n = 39, female = 26) underwent magnetic resonance imaging. Baseline analyses of brain structure via voxel‐based morphometry and brain function via functional connectivity (FC) at rest were correlated with changes in the Hamilton Depression Rating Scale between baseline and follow‐up, and incidence of a recurrent major depressive episode (MDE) within a 2‐year period. Results: Gray matter increases in default mode (DN) regions in the posterior cingulate cortex (PCC) and increased resting‐state FC within the DN both predicted change of depressive symptoms. Patients with recurrent MDE had larger bilateral nucleus accumbens and left insula volumes. Post hoc exploratory analysis of nucleus accumbens and insula conceptualized as part of the brain's reward circuit demonstrated reduced connectivity in patients with recurrent MDE. Conclusions: Higher DN connectivity and PCC volume coinciding with a more favorable course of symptoms suggest neural mechanisms of self‐recovery beyond the phase of active medical treatment. Alterations in the brain's reward circuit might be a starting point for designing maintenance treatments that prevent recurrent MDEs in rMDD patients.